Sensitivity of the stock assessment for the Antarctic krill fishery to time‐varying natural and fishing mortality - Elling Deehr Johannessen; Bjørn A. Krafft; Carl R. Donovan; Rodrigo Wiff; Bruno Caneco; Andrew Lowther (Fisheries Management and Ecology, 2024)
The stock assessment model for the Antarctic krill fishery is a population model operating on daily timesteps, which permits modeling within‐year patterns of some population dynamics. We explored the effects of including within‐year patterns in natural and fishing mortality on catch limits of krill, by incorporating temporal presence of key predator species and contemporary temporal trends of the fishing fleet. We found that inclusion of within‐year variation in natural and fishing mortalities increased catch limits. Fishing mortality had a greater effect than natural mortality despite differences in top‐down predation on krill, and potentially increased catch limits by 24% compared to the baseline model. Additionally, the stock assessment model allowed a higher catch limit when fishing was during peak summer months than autumn. Number of days with active fishing was negatively related to precautionary catch limits. Future stock assessments should incorporate contemporary spatiotemporal fishing trends and consider implementing additional ecosystem components into the model.